Moral Values in the Story of Prophet Lut - Rizka Amalia; Siti Ardianti; Azlia Fasya Kintara (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
We hear and read many stories about the prophets in the Qur'an, including the story of Prophet Lut a.s. which of course contains a lot of wisdom and teachings to be adhered to and emulated as a guideline for human life. And here the author focuses on discussing moral values in the story of the prophet Lut as. As we know, the atrocities of the people of Lut, such as those who like the same sex, have become a habit and are considered normal. Seeing a woman's body does not increase her lust, except seeing a man's body increases her lust. This study uses library techniques by collecting information from various sources by reading, analyzing it and drawing conclusions according to the problem. Researchers get some results in the form of messages that can be used as lessons for the future. The results of this study indicate that the Prophet Lut (as) repeatedly rebuked and warned his people not to commit immoral acts (same sex), but his people ignored these warnings. Therefore, Allah (s.w.t.) punished the people of Prophet Lut (a.s.) with a huge explosion accompanied by hail.